FACTOR ANALYSIS OF PRODUCTION AND ITS EFFICIENCY OF PASTEURIZED MILK PRODUCTION AT CV CITA NASIONAL, SEMARANG REGENCY - Sonius Luther Oktorio Siahaan; Edy Prasetyo; Bambang Mulyatno Setiawan (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2021)
The milk pasteurization process at CV Cita Nasional requires raw milk, sugar, and flavors with an optimum formulation, as well as efficient and effective human resources. How to obtain the formulation optimum and allocative efficiency from the use of production factors of fresh milk, sugar, flavor, and human resources on the amount of pasteurized milk production? The research objectives were to analyze the influence of production factors of raw milk, sugar, flavor, and human resources toward the amount of pasteurized milk production and to analyze the allocative efficiency of the use of production factors. The research method used was secondary data analysis of pasteurized milk production records using daily time series data for ninety-one days. Data analysis was performed using multiple linear regression and calculation of the level of production allocative efficiency. The results showed that raw milk had a significant influence, while sugar and flavor did not have a significant influence. However, all independent variables had an influence on pasteurized milk production. The allocative efficiency of the raw milk production factor was 4.10, sugar was -0.10, and food flavor was - 1.53. This result shows that the raw milk and flavor production factors did not meet the allocative efficiency, while the sugar was not allocative efficient. Dynamic production requires the management of human resources to obtain an effective and efficient job distribution.